Performance investigation of solar photovoltaic panels using mist nozzles cooling system - Syed Ali Raza Naqvi (12428586) (2024)
Solar PV has a disadvantage over its many advantages that its electrical efficiency falls due to rise in surface/operating temperature of solar PV cells. Therefore, it is necessary to find a way to mitigate the efficiency loss due to rise in temperature as well as to increase life span of solar photovoltaics by lowering its cell temperature. In this research, the impact of mist cooling on output of PV panel is observed through experimental setup installed at rooftop of Postgraduate Department, Mehran University of Engineering and Technology, Jamshoro, Pakistan. The rear surface of PV module is cooled with designed mist nozzle assembly. The performance of modified mist cooled PV module is than compared with reference PV module. Experimental investigation is performed several days in different weather conditions with natural circulation and with forced circulations by using submerged pump. The maximum efficiency gains of 7% and average gain of 3.72% is observed with natural circulation, and maximum gain of 9.2% and average gain 1.72% are observed with forced circulated mist. The overall impact of proposed mist cooled system is positive on performance of PV panels. Other Information Published in: Energy Sources, Part A: Recovery, Utilization, and Environmental Effects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15567036.2024.2305302